Investigating features of disfluent speech by EFL learners at Taiz University - Abeer Alghazali (English, 2019)
An effecting way to avoid making a mistake is by being aware of it. This paper aims at investigating the features of disfluent speech by EFL learners at Taiz University in order to draw the EFL learners to the features of disfluent speech they should avoid to make their speech sound more fluent and more natural. The focus in this paper is on repair features as fillers, repetitions, restarts and reformulations. The researcher collected data from 20 level four students English Language major, Faculty of Education, Taiz University. The participants were asked to narrate the events of a short silent video. The quantitative analysis showed that the participants overused disfluencies such as fillers, prolongations, repetitions, restarts and self-corrections. The mostly present self corrected item was the pronouns. It is highly recommended that the EFL learners should be aware of such disfluency features in order to avoid them while speaking.